2007
DOI: 10.1002/hrm.20167
|View full text |Cite
|
Sign up to set email alerts
|

Testing and extending the unfolding model of voluntary turnover to it professionals

Abstract: This study examines the turnover decision processes of information technology (IT) personnel for the first time. Our theoretical guide for this investigation was the unfolding model of voluntary turnover (Lee & Mitchell, 1994), the preeminent turnover process model. Most of the 124 leavers used three new decision paths that shared the characteristic of including an alternative job search and evaluation; another significant number used the original five theorized paths. In sharp contrast to earlier findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 37 publications
4
74
0
Order By: Relevance
“…Although employees have often been treated as a valued 'resource' or as 'human capital' (Niederman, Sumner, and Maertz, 2007;Shaw, 2011), they have not been studied as important stakeholders in their own right. This is surprising given that, as noted by McWilliams and Siegel (2001), employees are most affected by the business every day, are responsible for running it, and hence have the most stakes in it.…”
Section: Introductionmentioning
confidence: 99%
“…Although employees have often been treated as a valued 'resource' or as 'human capital' (Niederman, Sumner, and Maertz, 2007;Shaw, 2011), they have not been studied as important stakeholders in their own right. This is surprising given that, as noted by McWilliams and Siegel (2001), employees are most affected by the business every day, are responsible for running it, and hence have the most stakes in it.…”
Section: Introductionmentioning
confidence: 99%
“…In the third study, Niederman et al, (2007) empirically evaluated the unfolding model in the context of IT personnel turnover. Using a sample of 124 employees who are alumni of the MIS programs at two Midwestern universities, they categorized the turnover episodes of these employees into the distinct paths described in the unfolding model.…”
Section: Articles That Apply the Unfolding Modelmentioning
confidence: 99%
“…Drawing from Lee and Mitchell's definition, a shock is "a particular jarring event that initiates the psychological analyses involved in quitting a job" 3 [33]. In the IT turnover literature, Niederman et al [34] report that 66% of the leavers (IT professionals) experienced a shock, revealing the importance of this construct. Consequently, the evolution of the relevant attributes can be the direct result of one or several shocks that cause an IT employee to reconsider his job (e.g.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For example, research found that the construct of a shock, [4, p.451] is necessary for certain paths leading to IT personnel turnover, [34]; if this finding is replicated with IT entrepreneurs, this knowledge may lead IT entrepreneurs to (intentionally) provoke such a shock to occur. Moreover, by identifying trends in the evolution of their relevant factors, future IT entrepreneurs may be able to more clearly identify the subsequent steps which lead to actual turnover.…”
Section: Practical Implications Limitations and Future Researchmentioning
confidence: 99%